EFFICACY OF OZONIZED SEA BUCKTHORN OIL IN THE TREATMENT OF PERIODONTAL DISEASES IN TOBACCO-DEPENDENT PATIENTS - V.M. Zubachyk; M.P. Ilchyshyn (Ukrainian Medical Stomatological Academy, 2018)
Tobacco smoking remains one of the most important problems of the present time due to significant prevalence and harmful effects on human health. The area of primary contact with components of tobacco smoke is organs and tissues of the oral cavity, oral fluid. In this regard, there is a theoretical and practical interest in the problem of studying the nature and mechanisms of the damaging effects of tobacco smoke during smoking, in particular, on periodontal tissues. Depending on the duration and intensity of smoking misuse, one of the modern methods of treatment is oxygen-ozonized therapy (ozonotherapy), which reduces the risk of polypragrammia and is well combined with both medicines and phytopreparations. The aim of our study was to evaluate the effectiveness of ozonized sea buckthorn oil on periodontal tissues in tobacco-dependent patients. During the diagnosis, common clinical and paraclinical methods of examination were used, taking into account the results of examination and palpation, determining the depth of periodontal pockets, the degree of gum recession and abnormal movement of the teeth. For the correction of pathogenetic disorders, smokers suffering from GP were prescribed: in the comparative group, a common methodology based on hygiene education and upbringing, removal of local stimuli, orthopedic and surgical indications, as well as physiotherapy and general rehabilitation. In the main group − in addition to the generally accepted technique, applications in the gingival area were applied with ozonized sea buckthorn oil and rinsing the oral cavity with a 0.1% solution of myramystine. In order to enhance the therapeutic effect, the patients were recommended oral baths with sea buckthorn oil enriched with oxygen and toothpaste "Parodontax". As a result of the application of the proposed therapeutic agent, in patients with GP of I degree a stabilization of the results for direct data was observed after 6 and 12 months after treatment. However, in patients with GP of II degree and III degree, both the main group and the comparison group were diagnosed with an increase in the pathological process with respect to data after treatment and after 6 months (p<0,05). With an increase in the disease, no pattern was found regarding the causes of its recurrence. The best steady result was in a group of ex-smokers with chronic generalized periodontitis in different terms of the study. Improvement of the results of the proposed therapeutic agent application confirms the parodontoprotective properties and the bacteriological action of ozone. It also emphasizes the social significance of the problem of smoking cessation in people with inflammatory-destructive changes in periodontal tissues.